Seismic Hazard at Jalisco Block, Mexico - Núñez Cornú, Francisco Javier (Física de la Tierra, 2012)
Historically large and very destructive earthquakes as well as tsunamis occurred along the Jalisco Block at the west part of Mexico. Using available historic data and recent seismic studies, we revise and reevaluate the localization of these earthquakes. We conclude that exists high seismic hazard, therefore it is necessary a systematic and continuous study of the seismicity along the area. The north shore of Jalisco present the highest seismic hazard, nevertheless we cannot ignore medium earthquakes (6.9